THE DOG FEMORAL OSTEOBLAST NUMBER POST TRANSPLANTATION OF DEMINERALIZED PORCINE CORTICAL BONE XENOGRAFT - Sudimantini, Luh Made; Wirata, I Wayan; Gunawan, I Wayan Nico Fajar; Sumadi, I Wayan Juli; Marmanto, Tessa Saputri (Buletin Veteriner Udayana, 2022)
The xenograft function in fracture healing is as osteoinduction. Osteoinduction is stimulated by factors present in the graft material including proteins and growth factors. Proteins and growth factors contained in the graft material are related to the process of osteoblast formation. This study aims to determine the amount of osteoblasts in bone fractures post-transplantation demineralized porcine cortical bone xenograft. Eight males dog aged 3-4 months were used in this study, which was divided into 2 groups at random. Group I is 2 dogs is used as a control, the dog on the diaphysis of the femur bone is drilled with a diameter of 1 cm without graft material. Group II is 6 dog on diaphisis femur bone drilled with a diameter of 1 cm and given Demineralized Porcine Cortical Bone Xenograft. Femoral bone was biopsied at 4th and 8th weeks postoperative for histologically processed and stained with hematoxylin-Eosin. The results showed that the number of osteoblasts in the group given demineralized porcine cortical bone xenograft was higher than the control group. There was no statistically significant difference in the number of osteoblasts between groups (P> 0.05). In conclusion, demineralized porcine cortical bone xenograft can increase the number of osteoblast cells in the bone healing process but the increase is not significant.